1 Comment »

  1. Rewritten, this is the same as:
    1x + 2y = -4
    3x + 4y = -6

    Calculating the determinant of this system you get:
    D= (1*4)-(2*3) = -2
    and
    Dx = (-4*-4)-(2*-6) = -4
    Dy = (1*-6)-(-4*3) = 6

    We have that
    x = Dx/D = -4/-2 = 2
    and
    y = Dy/D = 6/-2 = -3

    Therefor the solution using Cramer’s rule is:
    x = 2
    y = 3

    Like

Leave a Reply

Please log in using one of these methods to post your comment:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s